2004
DOI: 10.1007/s11864-004-0030-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and management of early esophageal cancer

Abstract: Early esophageal cancer is defined by its limitation to the esophageal mucosa and submucosa. It has become a curable malignant disease, in sharp contrast to the dismal prognosis of esophageal cancer at advanced stages, which still represents the majority of patients. Understanding the risk factors, establishing surveillance programs for patients at risk, and developing preventative interventions such as dietary and lifestyle changes or pharmacologic interventions hold the potential of reducing the incidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…Patients with submucosal tumor (pT1b) have a high risk of lymph node metastases, in our series 18.2% (27 of 148), which makes them unsuitable for endoscopic treatment. Therefore, endoscopic resection is limited to patients with high-grade dysplasia or mucosal tumors (Korn, 2004), especially for patients with high-grade dysplasia, as no lymph node metastases and systemic disease reported. Most of the previous studies confirmed that lymph node metastases were rare in patients with mucosal tumor (Endo et al, 2000;Fujita et al, 2001;DeMeester, 2010;Bogoevski et al, 2011), but some studies reported a rate of higher than ten percent for lymph node metastases in mucosal tumor (Matsubara et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with submucosal tumor (pT1b) have a high risk of lymph node metastases, in our series 18.2% (27 of 148), which makes them unsuitable for endoscopic treatment. Therefore, endoscopic resection is limited to patients with high-grade dysplasia or mucosal tumors (Korn, 2004), especially for patients with high-grade dysplasia, as no lymph node metastases and systemic disease reported. Most of the previous studies confirmed that lymph node metastases were rare in patients with mucosal tumor (Endo et al, 2000;Fujita et al, 2001;DeMeester, 2010;Bogoevski et al, 2011), but some studies reported a rate of higher than ten percent for lymph node metastases in mucosal tumor (Matsubara et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Although the majority of patients with esophageal cancer (EC) presented with locally advanced disease in historical series, more recent series show that with increased surveillance endoscopy, many patients (18-33%) are being diagnosed with early-stage lesions (1,2). T1 EC is defined as a malignant tumor that is limited to the lamina propria mucosa or muscularis mucosa (stage T1a), or submucosa (stage T1b) in the eighth edition of the American Joint Committee on Cancer/Union for International Cancer Control TNM staging system (3).…”
mentioning
confidence: 99%